Moral Messages in the Film Cinta Subuh by Ali Farighi: A Semiotic Analysis of Roland Barthes - Mila Salsaby; Rubino (HM Publisher, 2023)
Film is one of the mass communication media that is currently favored by teenagers. This media is considered capable of being an alternative to preaching to the general public. One of them is Cinta Subuh’s film. This film is a medium for da’wah because, in this film, we can learn many moral messages. This study aimed to discuss moral values and understand the meaning of the moral message shown in the film